Effect of Microbial Inoculants on Growth, Yield and Quality Attributes of Brinjal - Kantyal, Deepika; Rattan, Puja; Sharma, Ashutosh; Reddy, A. Harshavardhan (International Journal of Economic Plants, 2024)
The present investigation was carried outduring May- August, 2021 at DAV University, Jalandhar, Punjab to find out the effect of microbial inoculants on growth, yield and quality attributes of brinjal (Solanum melongena L.). The experiment consisted of different microbial inoculants (Rhizobium, Trichoderma and Phosphate Solubilizing Bacteria) and three varieties (Pusa Purple Long, BR-112 and Pusa Purple Round) laid out in Randomized Block Design (RBD) with three replications. Observations were recorded on days to first flowering, days to 50% flowering, plant height (cm), stem diameter (cm), number of primary branches, number of secondary branches, number of leaves per plant, fruit length (cm), fruit diameter (cm), number of fruits per plant, average fruit weight (g), yield per plant (Kg/plant), yield per plot (Kg/plot), TSS, ascorbic acid (mg/100g) and titratable acidity (%). Analysis of variance (ANOVA) revealed significant effect of microbial inoculants, varieties and their interaction for all the characters under study. It was observed that plants which were treated with Rhizobium resulted in superior performance for most of the traits studied. Among varieties, desirable results were observed in Pusa Purple Long. Considering the interaction of microbial inoculants and varieties it was concluded that Pusa Purple Long treated with Rhizobium resulted in superior performance with respect to growth, yield and quality parameters of brinjal.